Coffee Agro forestry Performance in Pulau Panggung Sub-district, Tanggamus, Lampung, Indonesia - Fitriani Fitriani; Bustanul Arifin; Wan Abbas Zakaria; Hanung Ismono; Rudi Hilmanto (Indonesian Coffee and Cocoa Research Institute, 2018)
Coffee production system in Tanggamus was mostly cultivated around forest and Sekampung watersheds. Upstream Sekampung watersheds had been threatened by land degradation and deforestation. Trade-off have revealed between coffee production and ecological services in water catchment area. Enhancing the coffee productivity must be concern with environment conditions. Coffee agro forestry is well known as a great solution to improve the land productivity. Environment services form natural resources will be assertion and sustainable. This study is concern to explore how the coffee agro forestry in land ownership performs. Study taken place in Pulau Panggung sub district, Tanggamus. Respondents choose randomly amount 408 coffee farmers. Statistic descriptive used to tabulate and compile the coffee agro forestry perform criteria. Then the relationship between land ownership and coffee agro forestry criteria related with farmer incomes, labor availability, level of education, and experiences in coffee production were analyzed by multiple regression. Based on the analysis was revealed that coffee plant density amount 1.774 coffee trees.ha-1 while growth with shade trees (MPTS) attain to 187 trees.ha-1. MPTS based on wood represented by 8 kind of tress, while MPTS based on non-wood trees 5 type of trees. Multi cropping plants also appear such as pepper, cocoa, banana, and rubber. Adoption of Coffee agro forestry in Pulau Panggung sub district, Tanggamus was well performed. Farmer income was noted amount IDR 14.449.854,-.year-1 or IDR 1.204.155,-.month-1. The coffee farmer income was significantly influenced by shade trees (MPTS), land ownership, and land area.